Nursing and aids: memories of an epoch at the Nereu Ramos Hospital (1986 - 1996) - historical research - Jenifer Adriana Domingues Guedes; Miriam Süsskind Borenstein (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
Aids appeared in the beginning of the decade of 1980 and expanded all over the country, demanding the creation of specialized services for its treatment. In Florianópolis/SC, the Nereu Ramos Hospital (HNR) is a Reference Center in the State, for the treatment of people with aids. Considering that the illness has been causing serious changes in the life of people with aids, and also in the life of professionals who take care them, this study aimed to: Historicize, through memory, the experiences of the nursing professionals who lived the appearance of aids and its evolution at the HNR, in the period between 1986 - 1996. It's a qualitative research with a social-historical approach, that has as referential, memory and as technique for data collection, oral history. The research attended to the ethical principles recommended by Resolution 196/96. The analysis of the interviews carried out with the nursing professionals suggests, at first, four categories: Memory related to the HNR; Memory related to the nursing professionals' relationships and coping; The recognition of HNR as reference in the treatment of aids in SC; To remember the past as a fortifying space of identity and professional satisfaction. We conclude that aids has been causing significant changes in the entire institution and in the behaviour of the nursing professionals that worked there.